Analysis of the Connection: Emotional Regulation and Social Skills in Shaping Study Habits through Cognitive Engagement in the Era of AI-Based Economic Learning - Abelia Paramista; Riza Yonisa Kurniawan; Mohamad Arief Rafsanjani; Muhammad Abdul Ghofur (Economics Education Department Universitas Negeri Semarang, 2026)
The rapid growth of Artificial Intelligence has transformed learning behavior in higher education, raising concerns about students’ cognitive engagement when relying on AI-generated assistance. This study examines how emotion regulation and social skills influence students’ study habits in AI-based economic learning, with cognitive engagement as a mediating variable. Using an explanatory quantitative design, data were collected from undergraduate students of the Faculty of Economics and Business at accredited public universities in East java, Indonesia, through a validated questionnaire consisting of 27 items adapted from established measurement scales. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that emotion regulation and social skills have a positive direct effect on students’ study habits. However, only social skills indirectly enhance study habits through increased cognitive engagement, while emotion regulation does not significantly influence cognitive engagement in AI-assisted learning. These results highlight that interpersonal competence plays a critical role in sustaining cognitive engagement and developing effective study habits, even as learning becomes increasingly supported by AI. Practically, the study suggests that higher education institutions and policymakers should design learning programs that integrate emotional management, social skill development, and responsible AI use to foster adaptive learning behavior. The novelty of this study lies in revealing distinct psychological mechanisms underlying study habits in AI-based economic learning, a context that remains underexplored in Indonesia.